Tracing Imam Al-Qastalani in his Book Lata’if al-Isharat for the Arts of Recitations on the Amani Imam in his Book Al-Murshid fi Al-Waqf wa Al-Ibtada’ - Alfaleh , Ahmed Marji (Dirasat: Shari’a and Law Sciences, 2020)
This research is concerned with the two Imams al-Amani and al-Qastalani, their books and the approach of each of them in brief. The research focused on Imam al-Qastalani’s traces in his book Subtle Hints of the Arts of Readings on the Omani Imam in his Guide to Pausing and Starting Reading Verses of the Holy Quran. The aim of the research is to collect these traces, and study them in a full comparison with the sayings of other imams in the books of interpretation in general, and the books of endowment and innovation in particular. The research tried to arrive at the terms and method of Imam al-Qastalani in his pursuits, and to know the scientific value of them. The researcher adopted the inductive approach in collecting these traces and the analytical approach in studying and discussing them. The study also mentioned the Quranic texts by which it is inferred and the mention of the verse number and its name. The study reached several results, including: the attention of scholars to tracking and rectifying those who preceded them, and their keenness to discuss and explain issues, Imam Al-Qastalani’s keenness on literature in criticism, and the tracking formulas varied in his book, some of which are explicit and clear in tracking, and others are not explicit and indirect. The study confirmed the urgent need to re-investigate the guide book of the Omani Imam, as it identified a number of typographical and scientific errors in it.